Style and context of Old Greek Job - Dhont, Marieke (Supplements to the Journal for the Study of Judaism Ser., 2018)
Intro -- Contents -- Acknowledgements -- Abbreviations -- Introduction -- Chapter 1 Studying Style in the Old Greek Book of Job -- 1 Introducing the Translator of Old Greek Job -- 2 The Translation Technique of Old Greek Job -- 3 The Style of Old Greek Job -- 4 Language and Hellenization -- 5 The Nature of the Present Research -- Chapter 2 Descriptive Translation Studies and Polysystem Theory -- 1 Introduction -- 2 Descriptive Translation Studies -- 3 Polysystem Theory -- Chapter 3 The Jewish-Greek Polysystem -- 1 The Literary Polysystem of the Septuagint -- 2 The Jewish-Greek Literary Polysystem -- 3 Development within the Polysystem -- 4 Conclusion -- Chapter 4 Septuagintal and Natural Greek Usage in Old Greek Job -- 1 Introduction -- 2 Word Order -- 3 Syntactic and Grammatical Features of the Hebrew -- 4 Koine Greek -- 5 Transliteration -- 6 Septuagintalisms -- 7 Conclusion -- Chapter 5 High Register Greek in Old Greek Job -- 1 Introduction -- 2 Vocabulary -- 3 Syntactic Features -- 4 Rhetorical Features on the Colonic Level -- 5 Conclusion -- Chapter 6 Studying the Use of Rhetorical Features in Old Greek Job -- 1 Preliminary Observations -- 2 Remarks on the Approach of the Present Study -- 3 From the Viewpoint of the Hebrew Text -- 4 Variatio -- 5 From the Viewpoint of the Greek Text -- 6 Conclusion -- Chapter 7 Rhetorical Features in the Greek Text of Job -- 1 Symmetry and Chiasm in Parallel Cola -- 2 Anadiplosis -- 3 Anaphora -- 4 Epiphora -- 5 Parenthesis -- 6 Mesodiplosis -- 7 Conclusion -- Chapter 8 Increasing Complexity: Different Rhetorical Tactics at Once -- 1 Introduction -- 2 Clusters of Rhetorical Features in Units of Two to Four Cola -- 3 Increasing Interaction in Five or More Consecutive Cola -- 4 Translating Hebrew Poetry into Greek? -- Chapter 9 Old Greek Job in its Literary Environment.